Effectiveness of Differentiated Learning Approaches Based on Learning Styles in Improving Science Learning Outcomes: A Case Study at SD Muhammadiyah Noyokerten, Sleman - Kholidah, Nur; Maryani, Ika; Latifah, Ashilatul (The Indonesian Institute of Science and Technology Research, 2024)
This research is motivated by the lack of fulfillment of students' learning needs in classroom activities in grade V at SD Muhammadiyah Noyokerten and the low science learning outcomes on the water cycle material. The general aim of this study is to determine whether a differentiated learning approach based on learning styles can improve science learning outcomes. The type of research used is Classroom Action Research (CAR) consisting of two cycles. Each cycle is conducted over 2 meetings, comprising planning, implementation, observation, and reflection stages. The subjects of this study are 24 students in grade V. The instruments used include observation sheets, questionnaires, documentation, and learning outcome tests. The results of the study show that the differentiated learning approach based on learning styles can improve science learning outcomes.